TCDD exposure disrupts mammary epithelial cell differentiation and function - Collins, Loretta L. (2009)
Mammary gland growth and differentiation during pregnancy is a developmental process that is sensitive to the toxic effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). TCDD is a widespread environmental contaminant and a potent ligand for the aryl hydrocarbon receptor (AhR). We demonstrate reduced β-casein protein induction in mouse mammary glands and in cultured SCp2 mammary epithelial cells following exposure to TCDD. SCp2 cells exposed to TCDD also show reduced cell clustering and less alveolar-like structure formation. SCp2 cells express transcriptionally active AhR, and exposure to TCDD induces expression of the AhR target gene CYP1B1. Exposure to TCDD during pregnancy reduced expression of the cell adhesion molecule E-cadherin in the mammary gland and decreased phosphorylation of STAT5, a known regulator of β-casein gene expression. These data provide morphological and molecular evidence that TCDD-mediated AhR activation disrupts structural and functional differentiation of the mammary gland, and present an in vitro model for studying the effects of TCDD on mammary epithelial cell function.